2006
DOI: 10.1007/s10620-006-9374-z
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Impedance/pH Monitoring in Pediatric Patients: Preliminary Experience with 50 Cases

Abstract: This paper describes multiple intraluminal impedance (MII) in 50 children with typical and atypical gastroesophageal reflux (GER) symptoms and discusses the possible clinical significance of objective numeric data provided by MII computed analysis. Patients underwent 24-hr pH/MII monitoring. Reflux parameters were analyzed with relation to age and reported symptoms. Nonacidic MII events occurred as frequently as acidic ones. A Pathologic Bolus Exposure Index associated with a normal pH Reflux Index was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 23 publications
4
49
1
1
Order By: Relevance
“…Multichannel intraluminal impedance (MII) has recently been added to the repertoire of tests available to study esophageal (patho)physiology in children [1][2][3][4][5][6]. Thus far, MII has been used in 2 major areas: diagnosis of gastroesophageal reflux disease (GERD) and esophageal function testing [7][8].…”
mentioning
confidence: 99%
“…Multichannel intraluminal impedance (MII) has recently been added to the repertoire of tests available to study esophageal (patho)physiology in children [1][2][3][4][5][6]. Thus far, MII has been used in 2 major areas: diagnosis of gastroesophageal reflux disease (GERD) and esophageal function testing [7][8].…”
mentioning
confidence: 99%
“…Mattioli and colleagues' were tested pH monitoring and MII methods on 50 children with GERD (9) . According to their findings, acid and non-acid reflux had the same incidence and low rate of clinical symptoms in pediatric group is considered as a limitation of the MII.…”
Section: Resultsmentioning
confidence: 99%
“…According to their findings, acid and non-acid reflux had the same incidence and low rate of clinical symptoms in pediatric group is considered as a limitation of the MII. They suggested further studies on accuracy and precision of MII (9) . According to our findings, there were no statistically different in terms of demographic characteristics of patients in the two typical and atypical groups.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that feeding difficulties, chronic pulmonary aspiration, constipation, malnutrition and GER are the major problems in children with CP There are advantages and disadvantages of each method, and the facilities and experience of the center are also important when selecting the test to be used. Esophageal pH-monitoring is one of the most convenient methods but it only recognizes acidic episodes of reflux 12,13,23,24 . A significant proportion of reflux episodes are known to be non-acidic, especially in infants [23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…The intraluminal catheter also has a pH sensor. Thus, a combined esophageal multichannel intraluminal impedance-pH (MIIpH) technique may detect all GER episodes and classify GER episodes according to their pH value and proximal extension [9][10][11][12][13][14] .…”
mentioning
confidence: 99%